The Effect of Greenwashing on Company Value - Freshtriana Freshtriana; Sung Suk Kim (Owner : Riset dan Jurnal Akuntansi, 2025)
Comparing manufacturing companies in LQ45, this research examines the effect of greenwashing on company value. For the past few decades, environmental issues have become a major concern for investors, the public, and other stakeholders. This has encouraged businesses to implement stricter environmental responsibility practices. To find the appropriate regression model, the study used the Hausman and LM tests. The results indicate that the random effects model is more suitable. With a coefficient of 0.0163, the regression analysis shows that greenwashing has a significant positive effect on company value. In addition, control variables such as the use of debt funds, age, and investment in fixed assets increase the value of the company, while the LIK and GROWTH variables decrease it. This finding indicates that the market tends to respond to greenwashing in company assessments, and emphasizes that businesses should optimize their investments in sustainable projects to enhance their overall value. This research enhances our understanding of the relationship between greenwashing practices and company value, as well as the effect of greenwashing practices on sustainable business strategies.